KONSEP BERBAKTI TERHADAP ORANG TUA YANG BERCERAI PERSPEKTIF AL-QUR’AN - Maryam; Salwa Tri Safitri (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
Being devoted to both parents is every child's obligation. Islam honors the position of parents by setting obligations on them. However, some parents' marriage conditions are not ideal. For example: parents' divorce. It often has a negative impact on children's psychology, such as; due to lack of love from both parents, it resulted in children acting badly towards both parents. Meanwhile, this is not in accordance with the order in the Qur’an. The aim of this research is to provide solution on how to be filial to divorced parents based on the The Qur’an. This research was conducted by using qualitative methods and data collection using library research methods. The interpretation used the Maudhu'I tafsir (thematic interpretation) method, namely by discussing the verses of the Al-Quran according to the themes and titles that have been determined. The results of the this study show that in the Qur’an there are many verses related to Birrul Walidain. Moreover, Allah explains that there is no distinction, whether the parents are alive or dead, divorced or not divorced. A child is obliged to continue to do good or be devoted to both of them as long as they do not command disobedience. Among the solutions are; Re-understanding children about the concept of faith and God's destiny, understanding children about communication with both parents, education about filial piety to both parents, minimizing the causes of parental divorce